The impact of digital marketing on the reputation of insurance companies: The role of service quality and brand trust - Khaled M. Aboalganam; Amro Alzghoul (Insurance Markets and Companies, 2024)
The study evaluates the influence of digital marketing on the reputation of insurance companies in Jordan, guided by the mediating role of service quality and the moderating role of brand trust. This is a relevant topic because digital engagement has become increasingly important in shaping consumer perceptions and building brand reputation in the insurance industry. The purpose is to determine how digital marketing practices influence organizational reputation through service quality. A quantitative research design was adopted with data collected from 237 employees of 21 insurance companies in Jordan. The data were analyzed using structural equation modeling with partial least squares. The results indicate that digital marketing significantly improves the reputation of insurance companies. The findings demonstrated that service quality serves as a crucial mediator, as an improvement in service quality leads to an increase in customer satisfaction and loyalty, thereby enhancing a company’s reputation. Further, brand trust moderated the relationship of digital marketing with reputation, thereby indicating that reputational benefits from digital marketing are further enhanced in firms characterized by high brand trust. These findings highlight the importance of insurance firms implementing digital marketing-driven initiatives to improve service quality and build brand trust. This study has practical value in terms of guiding insurance companies in using digital marketing to build their reputation in a competitive market.